Time to achieve best postoperative visual acuity following Boston keratoprosthesis surgery. Issue 7 (3rd March 2021) - El-Khoury, Jonathan; Mustafa, Majd; Daoud, Roy; Harissi-Dagher, Mona
Abstract : Background/aims: To evaluate the time needed for patients with Boston type 1 keratoprosthesis (KPro) to reach their best-corrected visual acuity (BCVA) and all contributing factors. Methods: We retrospectively reviewed 137 consecutive eyes from 118 patients, measured how long they needed to reach their BCVA and looked at factors that might affect this time duration including patient demographics, ocular comorbidities and postoperative complications. Results: The mean follow-up was 5.49 years. The median time to BCVA postoperatively was 6 months, with 47% of patients achieving their BCVA by 3 months. The mean best achieved logMAR visual acuity was 0.71, representing a gain of 6 lines on the Snellen visual acuity chart. Postoperative glaucoma, retroprosthetic membrane (RPM) and endophthalmitis prolonged this duration. We found no correlation between the following factors and time to BCVA: gender, age, indication for KPro surgery, primary versus secondary KPro, number of previous penetrating keratoplasties, previous retinal surgery, intraoperative anterior vitrectomy and preoperative glaucoma. Conclusion: In our retrospective cohort, the majority of subjects reached their BCVA between 3 and 6 months after KPro implantation. This duration was significantly prolonged by the development of postoperative glaucoma, RPM and endophthalmitis.